Reinforcement of laminated glass facades against the blast load - Nakhaei, Jalal; Forghani, Saeed; Bitarafan, Mahdi; Lale Arefi, Shahin; Šaparauskas, Jonas (Journal of Civil Engineering and Management, 2015)
The first defensive element of the building against the explosion is the façade. On the condition that façade is not resistant against explosion and encounters the damage, the blast wave will enter the construction and increases financial losses and casualties. With respect to that glass facades do not possess adequate strength under the explosion; the major aim of the study is to examine variety of the reinforcement practices of glazing facades with the laminated glass subjected to the blast wave. The investigation has been done by two descriptive and simulation approaches with the finite element software of AutoDyn and eight simulations has been represented in the subject of laminated glasses. In addition, through AHP method, related questionnaires were designed so that some experts including 31 people possessing the activity and investigation background of two to thirty years in the civil protection scope answered them. Considered indexes in AHP model consist of resistance against explosion, passed light rate, expenditure, complexity and difficulty of accomplishment so that in the resistance part versus explosion, the results of numerical simulation have been benefited. Outcomes demonstrate the best function in laminated glass models belongs to the overlapped louvered opening model. Afterwards, the model of two-layer laminated glass with the spring is laid. Furthermore, the most economical model which supplies the most light as well as the most safety is the model of one-layer laminated glass with spring.